2015
DOI: 10.4103/0366-6999.168045
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Alterations in Microarchitecture, Mineralization and Mechanical Property of Subchondral Bone in Rat Medial Meniscal Tear Model of Osteoarthritis

Abstract: Background:The properties of subchondral bone influence the integrity of articular cartilage in the pathogenesis of osteoarthritis (OA). However, the characteristics of subchondral bone alterations remain unresolved. The present study aimed to observe the dynamic alterations in the microarchitecture, mineralization, and mechanical properties of subchondral bone during the progression of OA.Methods:A medial meniscal tear (MMT) operation was performed in 128 adult Sprague Dawley rats to induce OA. At 2, 4, 8, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 55 publications
1
10
2
Order By: Relevance
“…However, no differences were noted for either volume or thickness parameters, even when accounting for weight. While increased bone mineral density was observed in the current study, previous studies involving the male MMT models have demonstrated that significant morphological changes in the subchondral bone tend to emerge at later time points 47 .…”
Section: Discussioncontrasting
confidence: 71%
“…However, no differences were noted for either volume or thickness parameters, even when accounting for weight. While increased bone mineral density was observed in the current study, previous studies involving the male MMT models have demonstrated that significant morphological changes in the subchondral bone tend to emerge at later time points 47 .…”
Section: Discussioncontrasting
confidence: 71%
“…Subchondral bone thickening and changes in mineral density are known to occur early in human OA and to be evident before radiographic indications of joint space narrowing 33,34 . In a previous study by Yu et al, MMT resulted in increases in subchondral plate thickness and decreases in plate mineral density within the medial tibial plateau at 8-and 12-weeks post-surgery 35 . In the current study, however, there were significant increases in mineral density, volume, and thickness in the subchondral bone at 3-weeks postsurgery.…”
Section: Discussionmentioning
confidence: 81%
“…In the first group (the OA group), 24 rats were subjected to unilateral MMT surgery on the right knee joint. 19,20 Briefly, each rat was anesthetized by intraperitoneal injection of pentobarbital (50 mg/kg), and the anterior portion of the right knee was shaved and sterilized. The surgery was achieved under a dissecting microscope.…”
Section: Methodsmentioning
confidence: 99%
“…The present study was conducted to determine the usefulness of ADAMTS5 and FSTL1 as potential biomarkers of OA using medial meniscal tear (MMT) surgery in rats, which were previously used as a convenient model of OA. 13,18-20 We also endeavored to conduct the correlation between these 2 proteins with OA progression and with a set of conventional OA-related inflammatory markers, including TNF-α, CRP, and ESR. 5-7…”
Section: Introductionmentioning
confidence: 99%